In situ key aging parameter determination of a vehicle battery using only CAN signals in commercial vehicles. (15th May 2022) - Geng, Zeyang; Thiringer, Torbjörn
Abstract: In this article, an on-line impedance measurement technique for a battery pack is demonstrated and proofed, using only the already existing sensors and accessible bus data in an electrified vehicle. A sufficient amount of AC harmonics in the DC-link current, for the identification purposes, is created in normal driving conditions. Fourier analysis is used to process the data and extract the impedance information. It is found that the proposed on-line method can accurately measure the battery pack impedance at a low frequency range (5 Hz to 10 mHz) with 40 Hz sampling frequency in the bus data. A key impedance value in the electrochemical impedance spectroscopy can be captured clearly in different conditions, which can be used to track the battery state of health. A recorded current waveform during an on-road test is reproduced by a state-of-art battery tester in a lab and the obtained results are compared with impedance values measured by a classic potentiostat. The results from the on-road test have an excellent agreement with lab measurements. Highlights: A method that can identify and track a key impedance parameter for battery aging diagnostics. The method can be applied to standard commercial electric vehicles without extra equipment, just through ordinary driving. Solid proof of concept, through excellent agreement between field tests and lab verification.